2016
DOI: 10.1371/journal.pmed.1002085
|View full text |Cite|
|
Sign up to set email alerts
|

Dietary Diversity, Diet Cost, and Incidence of Type 2 Diabetes in the United Kingdom: A Prospective Cohort Study

Abstract: BackgroundDiet is a key modifiable risk factor for multiple chronic conditions, including type 2 diabetes (T2D). Consuming a range of foods from the five major food groups is advocated as critical to healthy eating, but the association of diversity across major food groups with T2D is not clear and the relationship of within-food-group diversity is unknown. In addition, there is a growing price gap between more and less healthy foods, which may limit the uptake of varied diets. The current study had two aims: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 30 publications
9
88
1
3
Order By: Relevance
“…around the diet quality of individuals with T2DM given the consumption of healthy diets is associated with a lower risk of developing the disease [35]. For example, a large prospective cohort study conducted in the United Kingdom showed individuals who reported consuming all five food groups had a 30% reduced incidence of T2DM [36]. Further research determining factors that impact long term adherence to dietary guidelines is needed [11].…”
Section: Discussionmentioning
confidence: 99%
“…around the diet quality of individuals with T2DM given the consumption of healthy diets is associated with a lower risk of developing the disease [35]. For example, a large prospective cohort study conducted in the United Kingdom showed individuals who reported consuming all five food groups had a 30% reduced incidence of T2DM [36]. Further research determining factors that impact long term adherence to dietary guidelines is needed [11].…”
Section: Discussionmentioning
confidence: 99%
“…There is a nonexhaustive list of factors that may affect allergy outcomes, but potential confounders should be corrected for analysing associations between diet diversity and allergy outcomes Diet diversity can be measured by counting individual foods, 31,37,[42][43][44][45][46] food groups 30,[34][35][36]38,39,41,43,[47][48][49][50][51][52][53][54] or foods within a group, 32,33,55,56 and can be measured over a time period ranging from the previous 24 hours (24-hour recalls) [31][32][33][34][35]38,40,44,46,48 or over a 7day period 33,39,42,47,53,[55][56][57] to intake over one year. Food intake data may be collected once [32][33][34]…”
Section: Practice Points Regarding Measuring Diet Diversity Based Onmentioning
confidence: 99%
“…The dietary diversity score (0-5) is a simple measure of the overall quality that indicates whether each of the 5 major food groups was mentioned in the recall (29,30). In previous published work, this measure has been shown to be related to health outcomes (31,32).…”
Section: Sensitivity Analysismentioning
confidence: 99%